Image-Based Mechanical Balancing of Reservoir Volumes During Benchtop Flow Battery Operation - Smith, Kirk P.; Monroe, Charles W. (Frontiers in Chemical Engineering, 2021)
The long-term maintenance of stable redox-flow-battery performance requires a strategy to manage dynamic volume imbalances between electrolyte reservoirs. Even with ion-selective membranes as separators, bulk liquid exchange can occur within the reactor because of pressure differences across its positive and negative chambers. Disproportionation chemistries, wherein both electrolyte reservoirs have identical composition in the discharged state, tolerate species crossover reversibly. These make possible the use of low-cost porous separators, but such materials are more hydraulically permeable. Here we propose an approach to mitigate reservoir imbalance, using the nonaqueous vanadium acetylacetonate disproportionation chemistry as a test platform. We demonstrate a benchtop-scale control scheme, which relies on a camera that monitors reservoir volumes linked to a microcontroller that regulates the differential flowrate between flow streams. The balancing apparatus introduces no extra wetted components and enables real-time measurements of intra-cycle imbalance due to electroosmosis. All software and firmware is made available for community use.